Cannabinoids for the Neuropsychiatric Symptoms of Dementia: A Systematic Review and Meta-Analysis. (June 2020) - Bahji, Anees; Meyyappan, Arthi Chinna; Hawken, Emily R.
Background: In 2016, the global number of individuals living with dementia was 43.8 million, representing a 117% increase from 1990—mainly due to increases in aging and population growth. Up to 90% of individuals with dementia experience neuropsychiatric symptoms (NPS). However, the limitations of current treatments for NPS have drivent he search for safer pharmacotherapies—including cannabinoids. Aim: To assess the efficacy and acceptability of cannabinoids for the treatment of NPS in individuals with dementia. Design: Systematic review and meta-analysis of clinical trials. Setting and participants: Of 6, 902 papers, 9 were eligible ( n = 205, 44% female, 78 ± 7 years, 85% Alzheimer disease). Trials were in North America and Europe and explored tetrahydrocannabinol ( n = 3), dronabinol ( n = 5), or nabilone ( n = 1). Measurement: Titles/abstracts were independently screened by one reviewer and reviewed by a second. Full-text screening was by two reviewers with discrepancies resolved via a third reviewer. We extracted data on the standardized mean difference (SMD) for several NPS instruments, trial completion, and adverse events. Data were pooled using random-effects models. Findings: Cannabinoids led to significant improvements across NPS instruments, including the Cohen Mansfield Agitation Inventory (SMD = −0.80; 95% confidence interval [CI], −1.45 to −0.16), the Neuropsychiatric Inventory (SMD = −0.61; CI, −1.07 to −0.15), and nocturnal actigraphy (SMD = −1.05; CI, −1.56 to −0.54h). Cannabinoids were well-tolerated, with an overall trial completion rate of 93% (193/205) and no serious treatment-related adverse events. Treatment efficacy was associated with baseline dementia severity and dose, but not dementia subtype, age, or sex. The overall study quality was rated as low. Conclusions: There is preliminary evidence for the efficacy and tolerability of cannabinoids as treatments for NPS. Population-based studies are needed to characterize their real-world effectiveness and acceptability.